2t2-5t-3=0

the quadratic formula is x = 1/2a ( -b ± sqrt(b^2 -4ac) here, from the equation a=2 , b = -5 and c = -3so, x = 1/4 ( -(-5) ± sqrt((-5)^2 -4*2*-3))) = 1/4( 5 ± sqrt ( 25+24)) = 1/4 (5± sqrt(49)) = 1/4(5±7)so, x = 1/4(5+7) or 1/4(5-7)= 12*1/4 or -2*1/4=3 or -1/2Please appreciate my help and use the "pay the tutor" option to may be the 1 $ thanks :)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up